Zdravý životní styl jako příležitost prevence onemocnění - Dobešová, Monika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Hlavním cílem bakalářské práce je analýza zdraví a životního stylu vysokoškolských studentů v Brně formou dotazníkového šetření a návrh plánu zdravého životního stylu s jeho ekonomickým vyhodnocením pro jedince. Dílčím cílem je poukázat na význam a pozitiva zdravého životního stylu. Práce současně analyzuje problematiku návykových látek a civilizačních chorob.

The main objective of this thesis is to analyze the health and lifestyles of university students in Brno in the form of a questionnaire and a draft plan for a healthy lifestyle, economic evaluation of the individual. Partial aim is to highlight the importance and benefits of a healthy lifestyle. It also analyzes the issues of drugs and diseases of civilization
Healthy Lifestyle as an Opportunity to Prevent Disease
Keywords: : Zdravý životní styl; zdraví; wellness; analýza; náklady; Healthy lifestyle; health; wellness; analysis; costs